Arabic Behaviour: Escalation of Ability to Speak Arabic - Ainil Khuryati; Eva Ardinal; Nurul Alamin (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2023)
Arabic is essential for supporting learning, such as accessing Arab library materials or communicating. Arabic language education is in great demand for students. However, the problem in the field is that many students have difficulty understanding learning. Students experience difficulties speaking Arabic because they do not master the vocabulary, and it is challenging to pronounce Arabic words. This article offers a solution to escalating the ability to speak Arabic through forming Arabic behavior. The research method used is library research.  Research is sourced from library data such as journal articles, books, and websites. The study results show that Arabic behavior can be created with the existence of Arabic language learning institutions because Arabic language institutions have a critical role in accelerating the ability to speak Arabic and supporting education. Then the learning modules are adapted to the students' ability level because it will help them absorb information more efficiently and effectively and improve their speaking skills in Arabic more quickly. The next is to associate with people with the same interest in learning Arabic, and the last is to practice speaking Arabic.